Bacterial Growth and Adaptation in Microdroplet Chemostats1. Issue 34 (5th July 2013) - Jakiela, Slawomir; Kaminski, Tomasz S.; Cybulski, Olgierd; Weibel, Douglas B.; Garstecki, Piotr
<x xml:space="preserve">Abstract</x> Getting your bugs in a row: A microfluidic device for manipulating and monitoring the continuous growth of populations of bacteria within microdroplets was developed (see scheme). This device allows for monitoring hundreds of populations of bacteria to study changes in growth rates and the effects of antibiotics, including the evolution of antibiotic resistance in real time.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>